In the eye of the beholder? Differentiating between SMEs and Mittelstand - André Pahnke; Friederike Welter; David B. Audretsch (Small Business Economics, 2022)
A common fallacy is that small and medium-sized enterprises (SMEs) are the translation for Mittelstand companies. Until today, no common, widely accepted, and consistently applied understanding of what constitutes the Mittelstand exists, and related international research is consequently less coherent as well as a strong evidence-base for policy makers lacking. Most empirical research has relied on data for SMEs, taking quantitative metrics on firm size as constituent features of Mittelstand companies. The paper challenges this simplified equation of Mittelstand and SMEs and provides a first comparison of different approaches to analyze Mittelstand companies. Focusing on the criteria owner-management, firm size, and a sense of belonging to the Mittelstand, we highlight systematic differences of these approaches. Consequently, we suggest a conceptualization of Mittelstand companies that paves the way for more comprehensive research by setting the distinctive company identity based on ownership and management at the core of what constitutes the Mittelstand. Plain English Research on Mittelstand companies is faced with a dilemma. On the one hand, Germany's Mittelstand companies have attracted increased attention in the entrepreneurship literature as well as from policy makers and media at an international level. On the other hand, there is no common, widely accepted and consistently applied understanding of what constitutes the Mittelstand. As a result, research on the Mittelstand is less coherent causing confusion in media, politics, and academia. The paper addresses this ambiguity of the term Mittelstand prevalent throughout the literature and compares different approaches to measuring, identifying, and classifying the Mittelstand. Highlighting their systematic differences, we finally suggest that research, policy makers, and practitioners should set the unity of ownership and management at the core of the Mittelstand. In this way, a more comprehensive and unified understanding of the Mittelstand and its heterogeneity should emerge at all levels.
Keywords: L26; M13; 330; SME; Mittelstand companies; Ownership structure; Owner-managers; Firm size